LATIHAN CLOSED KINETIC CHAIN LEBIH BAIK DARIPADA OPEN KINETIC CHAIN UNTUK MENINGKATKAN KEMAMPUAN FUNGSIONAL PADA OSTEOARTHRITIS LUTUT SETELAH PEMBERIAN MICRO WAVE DIATHERMY (MWD) DAN TRANSCUTANEUS ELECTRICAL NERVE STIMULATION (TENS) - Indri Susilawati; Ketut Tirtayasa; S.Indra Lesmana (Sport and Fitness Journal, 2015)
Knee osteoarthritis is a disease caused by degenerative factors that mostly found in musculoskeletal and knee osteoarthritis has the most common cause to limited motion and body function. People with osteoarthritis usually complain of pain, stifftess and limitation of function. This study aimed to determine closed kinetic chain exercise was better than open kinetic chain to increase functional capability of knee osteoarthritis after giving treatment micro wave diathermy (MWD) and transcutaneus electrical nerve stimulation (TENS). The design of this research was true experimental pre-test and post-test with control group design, which the population was taken by purposively sampling. Division of the sample into two groups, group one consisted of 6 people. The first group was given MWD, TENS and Closed Kinetic Chain exercise and group two was given MWD, TENS and Open Kinetic Chain exercise. The frequency of exercise are 3 times a week for 4 weeks. Subjects were all patients with knee osteoarthritis who had been diagnosed through assesment procedures conducted in General Hospital of Mataram–Lombok, West Nusa Tenggara. Analysis of significance with Paired t-test (paired) showed that in each group resulted in an increase in functional ability after treatment of knee osteoarthritis is significantly different (p<0.05). While a difference test in both groups after treatment using analysis test of Independent t-test (unpaired) showed that the value of t = 2.748 and p = 0.021. So thah there was an increase functional capabilities of knee osteoarthritis after treatment (p<0.05). In conclution the treatment conducted in group one which was MWD, TENS and Closed Kinetic Chain proved improvement of the functional capabilities of  knee osteoarthritis better than treatment conducted in group two, namely the MWD, TENS and Open Kinetic Chain.